Gaps, Representation, and Elite-Mass Congruence in Chile and Uruguay [Brechas, Representación y Congruencia Élite-Ciudadanía en Chile y Uruguay] - Gonzalez-Bustamante, B (Universidad Autonoma del Estado de Mexico, 2019)
This paper analyzes three dimensions of elite-mass congruence in Chile and Uruguay: (a) ideological; (b) public issues, support, and satisfaction with democracy; and, (c) economic preferences on the role of the State. Data from probabilistic national surveys and surveys on elites financed by IDRC-Canada and carried out from 2013 to 2014 in each country are used. Congruence indexes are calculated to identify gaps between citizens and representatives. The main indexes used are Relative Citizen Congruence and Earth Mover’s Distance, a recent innovation borrowed from computer science. The findings show a greater ideological congruence in Chile, a greater congruence on support to democracy in Uruguay, and important gaps on education issues in Chile. Furthermore, in both countries there is greater congruence regarding relevant public issues between higher socioeconomic level population and the political elite. © 2019 Universidad Autonoma del Estado de Mexico. All rights reserved.